The Influence of Teaching Practice Assessment on the Effectiveness on Geography Teaching in English Speaking Secondary Schools in Anglophone Cameroon - Chu, Ambei Moses (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Every educational system of any given country around the world depends largely on the quality of teacher education. For this quality to be realized, it is important to constantly monitor the stages (theoretical, teaching practice, research project) involved in the teacher education. This study sought to investigate the influence of Teaching Practice Assessment on the Effectiveness of Geography Teaching in English Speaking Secondary Schools in Anglophone Cameroon. It was carried out within the Menchum and Fako Divisions of the North West and South West regions of Cameroon. This research had as population size, some 1444 geography teachers and all their students drawn from all government secondary schools within these two regions. Teachers’ sample population was gotten through the use of purposive sampling method while that of students was gotten through the use of simple random sampling. Respondents were expected to fill in closed ended questionnaire items. Data collected were reported using frequency tables and proportions while Logistic Regression Model was used to predict the effect level of influence of teaching practice assessment on geography teachers’ teaching effectiveness. It was realized that teaching practice assessment had a predictive effect of 26.8% on teaching effectiveness. Based on the outcome of these findings, it can be said that no single factor bring about teaching effectiveness. However, bringing many factors together should guide towards bringing about effective teaching. From the above findings, it was recommended that more emphasis during teacher training should be laid on subject matter mastery by student-teachers. Also, some form of financial incentives should be given to student-teachers. Finally, a thorough screening exercise should be done in the selection of supervisors and cooperating teachers to ensure that only the most qualified are assigned to guide and supervise student-teachers.